Impact of a youth‐friendly HIV clinic: 10 years of adolescent outcomes in Port‐au‐Prince, Haiti. Issue 1 (4th July 2016) - Reif, Lindsey K; Bertrand, Rachel; Benedict, Charles; Lamb, Matthew R; Rouzier, Vanessa; Verdier, Rose; Johnson, Warren D; Pape, Jean W; Fitzgerald, Daniel W; Kuhn, Louise; McNairy, Margaret L
Abstract : Introduction: Adolescents account for over 40% of new HIV infections in Haiti. This analysis compares outcomes among HIV‐positive adolescents before and after implementation of an adolescent HIV clinic in Port‐au‐Prince, Haiti. Methods: We conducted a cohort study using programmatic data among HIV‐positive adolescents aged 13 to 19. Data from 41, 218 adolescents who were HIV tested from January 2003 to December 2012 were included. Outcomes across the HIV care cascade were assessed before and after implementation of an adolescent clinic (2009), including HIV testing, enrolment in care, assessment for a ntiretroviral therapy (ART) eligibility, ART initiation and 12‐month retention. Pre‐ART outcomes were assessed 12 months after HIV testing. Factors associated with pre‐ART and ART attrition were identified through multivariable competing risk and Cox proportional hazards regression modelling. Results: Cumulatively, 1672 (4.1%) adolescents tested HIV positive (80% female, median age 16 years). Retention by cascade step comparing pre‐ and post‐clinic included the following: 86% versus 87% of patients enrolled in care, 61% versus 79% were assessed for ART eligibility, 85% versus 92% initiated ART and 68% versus 66% were retained 12 months after ART initiation. Pre‐ART attrition decreased from 61% pre‐clinic to 50% post‐clinic ( p <0.001). Pre‐ART attrition was associated with being female (sub‐distributional hazard ratio (sHR): 1.59; CI: 1.31–1.93), syphilis diagnosis (sHR: 1.47; CI: 1.16–1.85) and slum residence (sHR: 0.84; CI: 0.72–0.97). ART attrition was associated with syphilis diagnosis (hazard ratio (HR): 2.23; CI: 1.35–3.68) and CD4 <50 cells/µL (HR: 1.88; CI: 1.15–3.06). Conclusions: Implementation of a youth‐friendly adolescent clinic improved retention in HIV care among adolescents, particularly in the assessment of ART eligibility and ART initiation. Additional interventions are needed to improve retention among pre‐ART patients and support long‐term retention among ART patients.